Evaluation of Solar Chimney Power Plant in Semi-Arid Region of Nigeria - Ngala, G. M.; Oumarou, M. B.; Mohammad, A. B.; Shuwa, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2015)
Solar chimney power plant (SCPP) is a renewable energy facility that converts the potential energy in the Sun into kinetic energy and subsequently into electrical energy. The problem of global warming and electricity generation/distribution in Nigeria cannot be over emphasized; however with the vast land in the semi arid region and the potentials of the above technology, high prospects exist for solar chimney as it is a decentralized form of power generation. The aim of this paper was to theoretically evaluate the performance of the solar chimney power plant in semi-arid region of Nigeria, and estimate the amount of electrical energy that can possibly be generated. A mathematical model was used to estimate the amount of power generated, and determine the relationship between various meteorological and physical factors to the power produced. A solar chimney power plant with collector diameter of 700 m and chimney height of 700 m can produce up to 3000 MW of electricity